CISH and susceptibility to infectious diseases. - Khor, C; Vannberg, F; Chapman, S; Guo, H; Wong, S; Walley, A; Vukcevic, D; Rautanen, A; Mills, T; Chang, K; Kam, K; Crampin, A; et al. (2010)
BACKGROUND: The interleukin-2-mediated immune response is critical for host defense against infectious pathogens. Cytokine-inducible SRC homology 2 (SH2) domain protein (CISH), a suppressor of cytokine signaling, controls interleukin-2 signaling. METHODS: Using a case-control design, we tested for an association between CISH polymorphisms and susceptibility to major infectious diseases (bacteremia, tuberculosis, and severe malaria) in blood samples from 8402 persons in Gambia, Hong Kong, Kenya, Malawi, and Vietnam. We had previously tested 20 other immune-related genes in one or more of these sample collections. RESULTS: We observed associations between variant alleles of multiple CISH polymorphisms and increased susceptibility to each infectious disease in each of the study populations. When all five single-nucleotide polymorphisms (SNPs) (at positions -639, -292, -163, +1320, and +3415 [all relative to CISH]) within the CISH-associated locus were considered together in a multiple-SNP score, we found an association between CISH genetic variants and susceptibility to bacteremia, malaria, and tuberculosis (P=3.8x10(-11) for all comparisons), with -292 accounting for most of the association signal (P=4.58x10(-7)). Peripheral-blood mononuclear cells obtained from adult subjects carrying the -292 variant, as compared with wild-type cells, showed a muted response to the stimulation of interleukin-2 production--that is, 25 to 40% less CISH expression. CONCLUSIONS: Variants of CISH are associated with susceptibility to diseases caused by diverse infectious pathogens, suggesting that negative regulators of cytokine signaling have a role in immunity against various infectious diseases. The overall risk of one of these infectious diseases was increased by at least 18% among persons carrying the variant CISH alleles.